2008
DOI: 10.1055/s-0037-1608919
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase induces tissue factor pathway inhibitor expression and extracellular accumulation in endothelial and tumor cells

Abstract: SummaryHeparanase activity is implicated in cell invasion, tumor metastasis and angiogenesis. Recently, we have reported that heparanase stimulates tissue factor (TF) expression in endothelial and cancer cells, resulting in elevation of coagulation activity. We hypothesized that heparanase regulates other coagulation modulators, and examined the expression and localization of tissue factor pathway inhibitor (TFPI) following heparanase over-expression or exogenous addition. Primary human umbilical vein endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 28 publications
2
69
0
2
Order By: Relevance
“…In parallel, heparanase also appears to stimulate TF pathway inhibitor (21). Additionally, exogenously applied heparanase has been shown to modify in vitro coagulation on endothelial cells in culture (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, heparanase also appears to stimulate TF pathway inhibitor (21). Additionally, exogenously applied heparanase has been shown to modify in vitro coagulation on endothelial cells in culture (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase function however is not limited solely to its enzymatic activity. Enzymatically inactive heparanase can activate signaling molecules such as AKT and p38 [256, 257] and promote transcription of several biologically important effectors [ e.g., hepatocyte growth factor (HGF) and tissue factor] [258, 259]. This implies heparanase has broad functions beyond its impact on HS.…”
Section: Heparanase Syndecan-1 Shedding and Exosomes Facilitate Imentioning
confidence: 99%
“…There are also reports on increased plasma levels of TFPI in relation to diabetes mellitus,23 renal diseases,24 and cancer 25,26. Recently we demonstrated that exogenous addition or over-expression of heparanase by transfected cells resulted in release of TFPI from the cell surface and its accumulation in the cell culture medium 27. Importantly, the in vitro studies were supported by elevation of TFPI levels in the plasma of transgenic mice over-expressing heparanase.…”
Section: Heparanase Releases Cell Surface Tissue Factor Pathway Inhibmentioning
confidence: 64%
“…Heparanase was recently revealed as an important modulator of blood coagulation 13,17,18,27. Generating peptides inhibiting heparanase procoagulant activity36 strengthens the role of heparanase as a new procoagulant factor in the coagulation cascade.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation